A state-of-art review on chatter and geometric errors in thin-wall machining processes. (August 2021) - Wu, Ge; Li, Guangxian; Pan, Wencheng; Raja, Izamshah; Wang, Xu; Ding, Songlin
Abstract: Thin-wall components are some critical parts that are extensively used in modern industries due to their high structural efficiency and low specific weight. However, precision machining of flexible thin-wall components has been a challenging task accompanied by many inevitable issues such as unexpected chatter vibration and large surface form errors. To solve these inherent problems and improve the machining quality, plenty of research has been carried out in the last decades. In this paper, a comprehensive review of previous studies on thin-wall machining process and issues has been conducted; The state-of-the-art technologies recently developed are introduced, and an in-depth discussion of both chatter vibration and thin-wall deformation have been presented in terms of the theories, mechanisms, the prediction, monitoring and elimination methods. Finally, development trends are summarized, and recommendations for future works are proposed based on the extensive review and the analysis of practical problems.